Prediseño para readecuar la vía C134 en Ciudadela, Panorama, Duran, mejorando infraestructura vial considerando impactos sociales, económicos y ambientales. - Angulo Tobar, Dylan Paul (2025)
The C134 road redevelopment project in Durán seeks to optimize this important road artery. Currently, the road is congested due to its obsolete infrastructure and high vehicle demand. The pre-design proposes widening the road to two lanes, modernizing it with smart traffic lights and updated signage, and improving pedestrian circulation with sidewalks and safe crossings. This is expected to speed up traffic and improve road safety for all users. In addition, the project considers social and economic impacts. The revaluation of the area and the improvement in connectivity are expected to benefit local residents and businesses, boosting economic development. Measures will be taken to minimize inconveniences such as the relocation of services and temporary disruptions during the works. The Annual Daily Average Traffic (ADAT) study classified the road as a two-lane C1 highway, with a vehicle fleet composed mainly of light vehicles (47%), buses and minivans (36%), and trucks (17%). The project also includes measures to minimise environmental impacts, such as waste management, protection of green areas and the use of green technologies in the works. The goal is to promote sustainable urban and economic growth while maintaining the area's environmental balance.